Acyl ghrelin improves cognition, synaptic plasticity deficits and neuroinflammation following amyloid β (Aβ1‐40) administration in mice. (25th May 2017) - Santos, V. V.; Stark, R.; Rial, D.; Silva, H. B.; Bayliss, J. A.; Lemus, M. B.; Davies, J. S.; Cunha, R. A.; Prediger, R. D.; Andrews, Z. B.
Abstract: Ghrelin is a metabolic hormone that has neuroprotective actions in a number of neurological conditions, including Parkinson's disease (PD), stroke and traumatic brain injury. Acyl ghrelin treatment in vivo and in vitro also shows protective capacity in Alzheimer's disease (AD). In the present study, we used ghrelin knockout (KO) and their wild‐type littermates to test whether or not endogenous ghrelin is protective in a mouse model of AD, in which human amyloid β peptide 1‐40 (Aβ1‐40 ) was injected into the lateral ventricles i.c.v. Recognition memory, using the novel object recognition task, was significantly impaired in ghrelin KO mice and after i.c.v. Aβ1‐40 treatment. These deficits could be prevented by acyl ghrelin injections for 7 days. Spatial orientation, as assessed by the Y‐maze task, was also significantly impaired in ghrelin KO mice and after i.c.v. Aβ1‐40 treatment. These deficits could be prevented by acyl ghrelin injections for 7 days. Ghrelin KO mice had deficits in olfactory discrimination; however, neither i.c.v. Aβ1‐40 treatment, nor acyl ghrelin injections affected olfactory discrimination. We used stereology to show that ghrelin KO and Aβ1‐40 increased the total number of glial fibrillary acidic protein expressing astrocytes and ionised calcium‐binding adapter expressing microglial in the rostral hippocampus. Finally, Aβ1‐40 blocked long‐term potentiation induced by high‐frequency stimulation and this effect could be acutely blocked with co‐administration of acyl ghrelin. Collectively, our studies demonstrate that ghrelin deletion affects memory performance and also that acyl ghrelin treatment may delay the onset of early events of AD. This supports the idea that acyl ghrelin treatment may be therapeutically beneficial with respect to restricting disease progression in AD.